Inhibition mechanism of the chloride channel TMEM16A by the pore blocker 1PBC - Andy K. M. Lam; Sonja Rutz; Raimund Dutzler (Nature Communications, 2022)
TMEM16A, a calcium-activated chloride channel involved in multiple cellular processes, is implicated in various diseases, but its pharmacology remains poorly understood. Here, the authors combine cryo-EM and electrophysiology to elucidate the mechanism of TMEM16A inhibition by the pore blocker 1PBC.